Penyuluhan dan Pelaksanaan Vaksinasi Rabies di Desa Tagalaya Kecamatan Tobelo - Zakarias Dilago (Universitas Teuku Umar, 2019)
This community service was carried out for 2 days for the people in Tagalaya Village, Tobelo District, aimed at increasing public knowledge about rabies, as well as efforts to reduce the spread of rabies in Tobelo District, especially in Tagalaya Village. This activity was carried out by Polytechnic Perdamaian Halmahera Lecturers and students. The method used is counseling, demonstration and vaccination. The implementation stage on the first day was through counseling in the form of exposure to material on rabies which included rabies transmission, rabies prevention methods and treatment for rabies victims, then followed by vaccination demonstrations on several dogs belonging to the community. The activity continued on the second day by going around the village to vaccinate dogs that are kept by the community. The results of the extension activity showed that the community in Tagalaya Village had a better understanding of rabies, while the vaccination carried out on the second day succeeded in vaccinating 67 dogs, both adult dogs and puppies belonging to the Tagalaya Village community.